Diversification of diterpene biosynthesis occurred early in octocoral evolution - Immo Burkhardt; Hannah K. Bone; Natalie E. Grayson; Helena A. Leucke; Johanna Gutleben; Paul R. Jensen; Andrea M. Quattrini; Alexander B. Chase; Bradley S. Moore (Proceedings of the National Academy of Sciences, 2025)
Octocorals are the major source of marine-derived bioactive terpenoids. However, the vast majority of explored chemistry is known from shallow-water species, leaving deep-sea octocorals largely unexplored. Recent genomic work uncovered terpene biosynthetic pathways encoded in octocoral genomes, enabling deeper investigation into the evolution and ecological distribution of these compounds. Here, we collected nine deep-sea octocoral specimens representing both taxonomic orders and profiled their terpenoid chemistry. These samples revealed extensive diversity in sesquiterpene scaffolds, along with repeated detection of five widespread structural families of diterpenes (xeniaphyllene-, cembrene B-, elisabethatriene-, cembrene A-, and klysimplexin R; collectively, “XBECK-type” diterpenoids). Phylogenetic analysis of terpene cyclase (TC) sequences from these samples, combined with publicly available sequences and functional characterization of selected genes, indicated that most TC genes encode functionally diverse sesquiterpene cyclases that corresponded to deeply rooted taxonomic origins, rather than biochemical function. We further identified five monophyletic clades, each comprising isofunctional enzymes that produce precursors for distinct XBECK-type diterpenoids and showing broad representation across octocoral taxa. These findings suggest that diterpenoid biosynthesis evolved early in coral evolution, with the last common ancestor already possessing multiple functionally distinct TC enzymes. Our results establish terpenoid production as an ancient, central trait of octocorals, irrespective of habitat, thereby highlighting the tremendous potential of deep-sea corals as sources for bioactive terpenoids. Finally, these findings raise intriguing questions about the evolutionary origins of these pathways within early cnidarians and across animal phyla more broadly.